2017
DOI: 10.1159/000484394
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a-5p Inhibits the Growth of Renal Cell Carcinoma by Modulating GRP78 Expression

Abstract: Background/Aims: MiR-30a-5p, a member of the microRNA-30 family (miR-30), is known to function as a tumor suppressor in several different cancers. However, the expression levels, biological function, and underlying mechanisms of miR-30a-5p in renal cell carcinoma (RCC) remain unclear. Glucose-regulated protein78 (GRP78) is a common cancer biomarker and promotes the growth and survival of cancer cells. The expression of GRP78 has been reported to be modulated by miR-30a in neurons. In this study, the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…The host miR-30 family (five members, consisting of miR30a to miR30e) plays important roles in cancers and viral infections (30,34,36,37). We recently reported that miR-30a-5p, a member of the miR-30 family, is downregulated and that is expression is inversely correlated with the levels of ER stress in renal cancer, indicating that ER stress might inhibit miR-30a-5p expression (34). To assess whether ER stress suppresses the expression of miR-30a-5p, we initially analyzed the levels of miR-30a-5p in swine testicular (ST) cells following treatment with the ER stress inducer thapsigargin (Tg).…”
Section: Resultsmentioning
confidence: 99%
“…The host miR-30 family (five members, consisting of miR30a to miR30e) plays important roles in cancers and viral infections (30,34,36,37). We recently reported that miR-30a-5p, a member of the miR-30 family, is downregulated and that is expression is inversely correlated with the levels of ER stress in renal cancer, indicating that ER stress might inhibit miR-30a-5p expression (34). To assess whether ER stress suppresses the expression of miR-30a-5p, we initially analyzed the levels of miR-30a-5p in swine testicular (ST) cells following treatment with the ER stress inducer thapsigargin (Tg).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have demonstrated the function that HSPA5 plays in cancer metastasis and in anti‐apoptotic process of cancer cells . HSPA5 expression positively correlates with the large tumour size, aggressiveness, high clinical stage and resistance to conventional chemotherapy of RCC . Additionally, several studies have focused on the regulation mechanism or signalling pathway of the differential expression of HSPA5 in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…25 HSPA5 expression positively correlates with the large tumour size, aggressiveness, high clinical stage and resistance to conventional chemotherapy of RCC. 26 Additionally, several studies have focused on the regulation mechanism or signalling pathway of the differential expression of HSPA5 in cancers. Chang et al found that when E1A was expressed in cancer cells, p300 was activated to reduce acetylated HSPA5 levels and enhance its binding to GP78, thereby promoting HSPA5 ubiquitination and the subsequent inhibition of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that the 5-year survival rate of KIRC patients is less than 10% [27]. In the past, great efforts have been made to provide insights into the molecular mechanisms underlying KIRC, but the focus has been on protein-coding genes or miRNA [28,29]. Therefore, understanding the molecular mechanism of KIRC may provide clinicians with new treatment strategies for this disease.…”
Section: Discussionmentioning
confidence: 99%